Evaluation of newly transplanted blackberry tolerance to a selection of preemergence herbicides - Kayla Knepp; Matthew B. Bertucci; Aaron J. Cato; Amanda L. McWhirt; Nilda R. Burgos (Weed Technology)
This trial assessed the effect of preemergence herbicides on newly transplanted blackberries. A 2-yr field trial was initiated in 2021 and conducted at two locations in Fayetteville and Clarksville, AR. Seven treatments consisted of six preemergence herbicides (flumioxazin, mesotrione, napropamide, oryzalin, pendimethalin, and S-metolachlor) and one nontreated check. Preemergence herbicide treatments were applied to field plots of newly transplanted blackberry plugs (‘Ouachita’), using a CO2 backpack sprayer at 187 L ha−1 covering a 1-m swath, ensuring spray pattern overlap over newly planted blackberries in 2021 and reapplied in the same manner to established blackberries of the same plots in 2022. Data were collected on crop injury and plant height of blackberry plants in each plot. Yield data were collected in the second year, and fruit were analyzed for soluble solids content, pH, and average berry weight. In the first year, mesotrione and flumioxazin treatments caused injury to newly transplanted blackberries, and mesotrione-treated blackberries (58% in Fayetteville, 29% in Clarksville) did not fully recover by 84 d after treatment (DAT). Napropamide, S-metolachlor, oryzalin, and pendimethalin did not cause crop injury greater than 6% throughout the 2021 season. In the second year (2022), no crop injury was caused by any herbicide treatments. Results from these trials verify that flumioxazin, napropamide, oryzalin, and pendimethalin at the tested rates would be appropriate options for weed control in newly planted blackberries. These results corroborate regional recommendations against the use of mesotrione in first-year blackberry plantings. The findings from this trial indicate that S-metolachlor would be safe for registration for use on blackberries because of its limited effect on crop injury and blackberry yield.